The influence of profitability, offering size, firm size, financial leverage and sharia complaint status on initial return in IPO companies at the Indonesia stock exchange - Sherly Oktavina Avindo sherly; Aimatul Yumna (Universitas Negeri Padang, 2023)
This study aims to determine the effect of profitability, offering size, firm size, financial leverage and sharia compliant status on the initial return of IPO companies listed on the Indonesian stock exchange in 2018-2021. The population in this study are companies that carry out initial public offerings (IPO) there are 217 companies listed on the Indonesian stock exchange in 2018-2021. The research sample consisted of 76 companies with the sampling technique using purposive sampling . The data analysis technique used to test the hypothesis is multiple linear regression using SPSS version 26.